EUROMOD baseline report - Kateryna Bornukova; Fidel Picos; Antonio Amores; Irina Belousova; Hugo del Valle-Inclán Cruces; Paola De Agostini; Silvia De Poli; Ilda Dreoni; Klaus Grunberger; Adrian Hernández; Marta Jedrych Villa; Chrysa Leventi; et al. (European Commission, Joint Research Centre (JRC), 2024)
This report provides a selection of baseline simulation results and headline indicators from the latest public version (I6.0+) of EUROMOD, the tax-benefit microsimulation model for the EU. We begin by presenting indicators for income inequality and at-risk-of-poverty and how they are affected by the tax-benefit system. We then provide a comparative decomposition of the redistributive effect of the tax-benefit systems across the EU. We study how Member States achieve various degrees of redistribution through different combinations of progressivity and size of their tax-benefit system and each of its components. We then analyse various work incentive indicators affecting both the decision whether to work and that of how much to work, discussing how effective marginal rates of taxation and net replacement rates of going into unemployment vary across countries.
Keywords: 330